2013
DOI: 10.1121/1.4789356
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between unoccupied classroom acoustical conditions and elementary student achievement measured in eastern Nebraska

Abstract: Building standards recommend maximum background noise levels (BNL) and reverberation times (RT) for unoccupied classrooms. However, existing research does not show a consistent correlation between these parameters and student achievement. Through in situ testing, this research seeks to determine what acoustical conditions should be attained in elementary schools for students to meet educational goals. Acoustical measurements were conducted in a Nebraska public school system and correlated to achievement scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…8,10,15,23 Noise surveys of primary school classrooms have found that background noise levels in unoccupied classrooms typically average around 40-48 dBA (Ref. 13); a recent study of 67 elementary school classrooms in the U.S. (Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,10,15,23 Noise surveys of primary school classrooms have found that background noise levels in unoccupied classrooms typically average around 40-48 dBA (Ref. 13); a recent study of 67 elementary school classrooms in the U.S. (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…13); a recent study of 67 elementary school classrooms in the U.S. (Ref. 10) found that unoccupied levels ranged from 33 to 54 dB L Aeq . A survey of noise in Italian secondary schools found much lower background noise levels (measured with the students present but quiet) of 33-44 dBA L Aeq , 9 while university classrooms have been found to have background levels of 35 dBA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High noise levels adversely affect speech perception [16,18], reading and language comprehension [28,38,49], cognition, concentration, and the psychoeducational and psychosocial achievement of the child [4,16,53]. It is also suggested that poor acoustical conditions and noise places additional demands on children's learning effort.…”
Section: Introductionmentioning
confidence: 96%
“…The Lombard effect or Lombard reflex is the involuntary tendency of speakers to increase their vocal effort when speaking amid loud noise, to enhance the audibility of their voice [16]. Field research has found that the listener may follow conversation of interest despite many concurrent sources of sound [17].…”
Section: Introductionmentioning
confidence: 99%